Seeking academic help: A case study of peer brokering interactions. Issue 2 (1st October 2018) - Lee, Sherrie
The literature often depicts international students as deficient due to poor English language skills and limited participation in class, thus positioning them as lacking in agency or habitually weak. This article reframes international students as resourceful learners by focusing on their academic learning through brokering, that is, help-seeking social interactions. Understood as part of informal learning practices, brokering interactions take place when students seek assistance with unfamiliar academic texts and practices from brokers, that is, those who are able to bridge cultural and knowledge gaps. The article reports on research that investigated brokering practices among ten international English as an Additional Language (EAL) students in their initial semester of study at a New Zealand university. In particular, the article examines the brokering interactions between two participants, Linda, a first-year student, and her broker Emily, a fellow Mainland Chinese student who provided information and advice about various academic tasks and situations. A conversation analytic approach that views brokering as asymmetrical knowledge positions is used to analyse twelve episodes of brokering interactions in Chinese that took place through WeChat, a mobile phone application. Initial analysis reveals that the dynamics of brokering interactions between Linda and Emily were characterized by a display of social solidarity, even as seeker and broker negotiated their knowledge positions over information or advice offered by the broker. The article concludes that peer brokering between same language speakers provides a collegial space in which students exercise agency by utilizing sociolinguistic resources. Thus educational institutions should recognise the importance of international students' informal academic learning and increase opportunities for EAL students to build and enhance their social connections with peers as part of a holistic approach towards academic support.